Comparative Study on Performance of SOFC-GT with/without Anode Exhaust Gas Recirculation - Suthin Pholboorn; Dang Saebea; Yaneeporn Patcharavorachot (My University, 2023)
The comparative study on the electrical performance of solid oxide fuel cell combined with gas turbine with/without anode exhaust gas recirculation (SOFC-GTR/SOFC-GT-NR) was presented in this work. Performance analysis was performed through Aspen Plus simulator software. The SOFC system was included the pre-reforming process of methane. The simulation results revealed that the SOFC-GT-R has the maximum efficiency of 81.97% at pre-reforming percentage of 10% and fuel utilization of 0.90 while the highest performance of SOFC-GT-NR is 77.60% at pre-reforming percentage of 70% and fuel utilization of 0.90. From the comparative study, it was found that the SOFC-GT-R has higher efficiency by using lower pre-reforming percentage compared with SOFC-GT-NR.
Keywords: Advancements in Solid Oxide Fuel Cells; Fuel Cells and Related Materials; Electrocatalysts for Energy Conversion